Flow of Second Grade Fluid in a Scraped Surface Heat Exchanger. Issue 2 (16th June 2016) - Imran, A.; Rana, M.A.; Siddiqui, A.M.; Shoaib, M.
Abstract: Scraped surface heat exchanger (SSHE) is used in industry for the manufacturing of many foodstuff and these foodstuff behave as non‐Newtonian material. So in this work we have mathematically modeled flow inside SSHE by taking second grade fluid. In the SSHE, the gaps between the blades and device wall are narrow so lubrication approximations theory (LAT) can be used to study the various flow properties. Steady incompressible isothermal flow of a second grade fluid is considered about a sequence of pivoted scraper blades in a channel in which lower wall is moving and upper wall is stationary. Flow properties, namely velocities, stream functions, flow rates, expressions for pressure, the forces on the blades and walls in different stations of device are investigated. Graphic representation of different flow parameters involved is also incorporated. Practical Application: SSHEs are used in the food industry for the preparation of foodstuff to cook, chill or sterilize the various foodstuffs quickly and efficiently. SSHEs are manufactured for extremely viscous foodstuff such as purees, sauces, margarines, james, spread, soups, baby‐food, chocolates, mayonnaise, caramel, fudge, ice‐cream, and yoghurt, etc. Foodstuff are non‐Newtonian in nature as they possess shear thickening, thinning viscoelastic and visco plastic so it is more realistic to study flow inside SSHE by non‐Newtonian fluid model. This study provides fruitful insight to study the flow inside SSHE considering the non‐Newtonian nature of foodstuff.